2012
DOI: 10.1002/cmdc.201200107
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Pharmacophore Design and Biochemical Screening Identifies Substituted 1,2,4‐Triazoles as Inhibitors of the Annexin A2–S100A10 Protein Interaction

Abstract: Protein interactions are increasingly appreciated as targets in small-molecule drug discovery. The interaction between the adapter protein S100A10 and its binding partner annexin A2 is a potentially important drug target. To obtain small-molecule starting points for inhibitors of this interaction, a three-dimensional pharmacophore model was constructed from the X-ray crystal structure of the complex between S100A10 and annexin A2. The pharmacophore model represents the favourable hydrophobic and hydrogen bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
(31 reference statements)
0
30
0
Order By: Relevance
“…Recently, small molecule inhibitors of A2t (A2ti) have been identified that can disrupt the A2t tetramer by blocking the binding between anxA2 and S100A10 (56). As shown above, the role for A2t in the suppression of LC immune function is dependent on the tetramer form, and not on the individual subunits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, small molecule inhibitors of A2t (A2ti) have been identified that can disrupt the A2t tetramer by blocking the binding between anxA2 and S100A10 (56). As shown above, the role for A2t in the suppression of LC immune function is dependent on the tetramer form, and not on the individual subunits.…”
Section: Resultsmentioning
confidence: 99%
“…10 6 LC were seeded in a 6-well plate and either left untreated, treated with 10 μg LPS (Sigma-Aldrich), or treated with increasing concentrations of a previously identified A2t inhibitor (A2ti: 2-[4-(2-Ethylphenyl)-5-o-tolyloxymethyl-4H-[1,2,4]triazol-3-ylsulfanyl]acetamide) (56) alone or A2ti for 1 hr prior to exposure to 10 μg HPV16 PsV. The half maximal inhibitory concentration (IC 50 ) value of the A2ti was reported to be 24 μM (56).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that, together with its binding partner AnnexinA2, it is also involved in angiogenesis [62,63], making it a possible cancer drug target. Reddy, et al used the Tripos UNITY module, to map a pharmacophore query onto the crystal structure of the PPI complex [64]. S100A10 was considered the receptor as AnnexinA2 interacts with a cleft-like area of S100A10 via a single -helix at its N-terminal end.…”
Section: Manual Pharmacophore Model Designmentioning
confidence: 99%
“…110 Different methods can be employed to map the pharmacophore features onto the amino acids present at the PPI interface. 111 Several SMPPII discoveries have been achieved, thanks to pharmacophore searches using manually created search features, 112,113 or a consensus of interactions at the PPI interface, 114,115 or using automated methods, 116 or by identification of the key interactions using molecular interaction field analysis. 69 PPIs are especially promising targets for controlling inappropriate signaling, as found in diseases such as cancer.…”
Section: Protein-protein Interaction (Ppi) Inhibitionmentioning
confidence: 99%